Record linkage studies of drug-related deaths among former adult prisoners who have been released to the community: a scoping review protocol - Michael Donnelly; Richard Kirk; Dermot O'Reilly; Janine A Cooper; Ifeoma Onyeka (BMJ Open)
Introduction Prisoners often have a complex mix of health and care needs including needs relating to mental and physical ill-health conditions. In addition, substance use disorders are common in prisoners. The transition between prison and community poses risks in terms of a disruption to treatment and care and a deterioration in health. Studies have demonstrated an increased risk of drug-related deaths among former prisoners during the first weeks following release from custody. The aim of this scoping review is to provide an up-to-date account of evidence from record linkage studies about drug-related deaths among former adult prisoners.Methods and analysis This is a protocol for a scoping review. The framework for conducting scoping reviews by Arksey and O’Malley, in addition to the methodology and guidance developed by the Joanna Briggs Institute (JBI) and the JBI Collaboration will be followed. MEDLINE, EMBASE, PsychINFO and Web of Science will be searched for studies from 2011 to 2021 using search terms relating to ‘mortality’, ‘drugs’ and ‘ex-prisoner’. A preliminary search in MEDLINE identified at least 473 potentially eligible papers. Two authors will independently screen all titles and abstracts for eligibility using the inclusion and exclusion criteria. There will be no geographical restrictions but non-English language papers will be excluded. Data will be extracted using a piloted customised charting form and the findings will be mapped (guided by the population, concept and context inclusion criteria) and grouped by main conceptual categories (including methodology, key findings and gaps in the research).Discussion, ethics and dissemination This scoping review will identify, map and summarise publicly available sources of research and therefore does not require ethical approval. The results will inform our empirical investigation of ex-prisoner mortality as well as being shared with key stakeholders, disseminated in a peer-reviewed journal and presented at relevant conferences.